A Novel Cinch Automatic Bone Fracture Detection Algorithm - Shanthasheela, A; Nithya, E (International Journal of Computer Sciences and Engineering, 2025)
In recent years the computer vision field grown enormously and provides solutions to various other fields particularly like medical domain. Therefore many researchers contributed plenty of algorithms to support diagnosis. This proposed cinch bone fracture detection is a novel, easy, and effective algorithm for bone fracture using object counting in Leg bone or tibia. It automatically detects fracture & non-fracture in a leg bones.